PERAN GURU DALAM MENINGKATKAN NILAI AGAMA MORAL PADA ANAK KELAS B DI PAUD SHEKINAH KABUPATEN RAJA AMPAT : PERAN GURU DALAM MENINGKATKAN NILAI AGAMA MORAL PADA ANAK KELAS B DI PAUD SHEKINAH KABUPATEN RAJA AMPAT - Rima; Wilma B Wattimena (Lembaga Penelitian dan Pengabdian Institut Kariman Wirayudha Sumenep, 2024)
early childhood education plays an important role in their growth and development. Development of moral and religious values such as the ability to behave, behave and act. In order to improve religious values and morals in early childhood, several methods are needed. The aim of this research is as an effort to advance the role of teachers in increasing moral religious values in class B children at PAUD Shekinah Waisai, Raja Ampat Regency. In this research the author used a qualitative research approach. Because based on the author's experience in the field in improving moral religious values in children at Shekinah PAUD, the participants play an active role in providing direct examples and this becomes a guide for early childhood children at Shekinah PAUD. Where this method can be used to understand and discover what is hidden behind phenomena which are sometimes something that is difficult to understand satisfactorily